Foto-reportaje sobre la realidad socio - cultural y estética entorno a la situación del antiguo puente sobre el río Napo y sus alrededores en la ciudad de Pto. Fco. de Orellana - Robles Méndez, Jacqueline Edith (2015)
The culture from conception is a form of communication; every human group has different codes to communicate and also characterizes other groups. All elements (nature, people, animals, etc.) surrounding people influence their behavior and way of seeing the world. When several human groups share a common space and interact in it, they are creating culture. This theoretical work - practical takes a sociocultural analysis of the way of life of the inhabitants of Coca develops around the market settled on the basis of the old bridge Monsignor Alejandro Labaka. The fair of "indigenous" as it is known in this area of trade, is a point of convergence between various cultures on the one hand the settlers of the city that sell and offer products, other indigenous natives of the area are also getting their products for sale and other domestic and foreign tourists who stroll through the drawn know this form of "wild" life sector. The photo report clearly shows the importance that still has for the inhabitants of the city and surrounding parishes, the site of the old bridge Mons. Alejandro Labaka. The daily life of those who work here, especially indigenous women who come from distant communities to sell the products of their farms and as the Napo River and its tributaries remains the main access to the riverside communities.